Fluorescent Formazans and Tetrazolium Salts - Towards Fluorescent Cytotoxicity Assays - K. Ladyman, Melissa; G.A. Walton, Jeffrey; Lilienkampf, Annamaria; Bradley, Mark (Combinatorial Chemistry & High Throughput Screening, 2016)
Formazan-based colorimetric cytotoxicity assays, such as the MTT assay, are typically used to assess cell viability with only metabolically active cells reducing tetrazolium salts into the formazans, which is then quantified by absorbance. Fluorescence offers several advantages compared to colorimetric assays and would enable techniques such as flow cytometry and confocal microscopy to be used for analysis. Here, fluorescent formazans 10, 11 and 12, and their corresponding tetrazolium salts 13, 16 and 24, respectively, were synthesised by incorporation of a known fluorophore backbone (coumarin, fluorescein and rhodol) with disruption of the conjugated system preventing or reducing fluorescence of the tetrazolium salts. These tetrazolium salts were successfully reduced to the fluorescent formazans with cells and offer a step forward in the development of fluorescent cytotoxicity assays.
Keywords: MTT